Prevalence And Clinico-Laboratory Characteristics Of Mono Dengue And Dengue-Malaria Dual Infection And Their Association With Acute Kidney Injury Among Patients In Pakistan Tertiary Care Hospitals - Riaz, Muhammad (2024)
Dengue and malaria have similar clinical manifestations and laboratory characteristics, thus making it difficult to distinguish between the two infections during the endemic period. Dengue viral infection is a debilitating and dangerous vector-borne disease that has spread rapidly and becoming endemic in many parts of the world in recent years. According to world health organization (who) survey in pakistan plasmodium vivax prevalence is 84%. While, 14.9% and 1.1% cases were due to p. Falciparum and mixed infection respectively. Dengue fever is the major cause of illness and death geographically. Despite of aggressive precautionary measures, pakistan is still facing worsening dengue crisis over the past few years. It warrants an urgent need to evaluate dengue cases and dual infection cases to understand its clinico-laboratory spectrum in order to combat with these infectious diseases. Moreover, recent data indicated the rapid but transient rise in serum creatinine associated with the dengue induced acute kidney injury (aki) among dengue patients. This is associated with increased morbidity and mortality in dengue patients. Aki is still a neglected complication of dengue mono infection and dengue malaria dual infection in pakistan.